Odpowiedzi

Najlepsza Odpowiedź!
2009-11-11T16:50:22+01:00
X - pierwsza liczba
y - druga liczba

x+y = 60
1/2x + 1/3y = 24

x = 60 - y
1/2(60-y) +1/3y = 24

x = 60 - y
30-1/2y+1/3y = 24

x = 60-y
30-3/6y+2/6y = 24

x = 60-y
-1/6y = -6

x = 60 - y
y = 36

x = 24
y = 36
2009-11-11T16:51:11+01:00
X - liczba pierwsza
y - liczba druga

x+y=60
½x+⅓y=24 /*6

x=60-y
3x+2y=144

x=60-y
3(60-y)+2y=144

x=60-y
180-3y+2y=144

x=60-y
-y=144-180

x=60-y
-y=-36 /*(-1)

x=60-y
y=36

x=60-36
y=36

x=24
y=36
2009-11-11T16:52:41+01:00
X + y =60
1/2x + 1/3y =24 /*3

x + y =60
1,5x + y = 72

x + 72 - 1,5x = 60
y = 72 - 1,5x

-0,5x = -12
y = 72 - 1,5x

x = 24
y = 72 - 36

x= 24
y = 36